Writing the World, Writing the Web: Comparative Strategies of Self-Regulated Learning in Hybrid EFL Contexts - Hidayat, Hendi; Yuliasri, Issy; Rukmini, Dwi; Widhiyanto, Widhiyanto (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
This qualitative comparative case study investigates how English as a Foreign Language (EFL) students enact self regulated learning (SRL) strategies while composing academic reports in two contrasting settings: field based learning (FBL) and web based learning (WBL). 24 of  third semester undergraduates at an Indonesian cyber university were evenly assigned to conduct either community interviews (FBL) or online research (WBL) on local cultural traditions. Data from classroom observations, semi structured interviews to 3 students, and student texts were thematically analysed around five SRL components: goal setting and planning, information gathering and evaluation, self monitoring and adaptability, strategy use and feedback seeking, and motivation and self efficacy. Findings reveal context specific SRL profiles. FBL students displayed intention driven goals, situated accuracy, consistent thematic focus, dialogic revision with informants, and confidence rooted in relational engagement. WBL students exhibited adaptive structuring, digital breadth, emergent reframing, peer oriented polishing, and self efficacy linked to information management. Both groups regulated their writing, yet they relied on different affordances, namely social authenticity and textual flexibility. The study underscores SRL as an ecologically embedded process and recommends hybrid task designs that blend experiential inquiry with guided digital exploration. Such integration can cultivate writers who balance ethical representation with genre savvy adaptability, thereby supporting deeper learning in technology mediated EFL contexts